Street Level Burocrats, welfare locale e transizione digitale: ostacoli e spazi di innovazione sociale - Maurizio Busacca (Quaderni di Sociologia)
The article examines the adoption of digital innovation in the context of local welfare, focusing on the practices of labour market operators and social workers engaged in active labour market policy interventions in the region of Veneto. Through an ethnographic research, it highlights how three dimensions influence the adoption of technologies: institutional logics, organisational context, and professional discretion. Organisations tend to avoid investments in digital technology, perceived as too costly due to the underfunding mechanisms of the Italian welfare system, ineffective for beneficiaries with limited digital capabilities, and too complex for operators who lack adequate digital skills. However, this organisational behaviour reflects a discrepancy between institutional priorities, oriented towards activation and innovation logics, the organisational ones described above, and the individual ones of the professionals, who instead recognise the importance of digital skills for the job placement of beneficiaries and individually compensate for organisational deficiencies by introducing technological practices outside of organisational strategies. Professional discretion thus plays a significant role, with operators acting outside of organisational strategies and policies, relying on unregulated norms. However, the lack of funding and adequate enabling conditions limits the spread of technologies and subjects’ professionals to new forms of pressure. Moreover, this situation highlights that the weakness and fragmentation of the welfare system transform technology from an opportunity into a trap for operators and beneficiaries.